Axial distribution of plasma fluctuations, plasma parameters, deposition rate and grain size during copper deposition. Issue 7 (3rd August 2017) - Gopikishan, S.; Banerjee, I.; Pathak, Anand; Mahapatra, S. K.
ABSTRACT: Floating potential fluctuations, plasma parameters and deposition rate have been investigated as a function of axial distance during deposition of copper in direct current (DC) magnetron sputtering system. Fluctuations were analyzed using phase space, power spectra and amplitude bifurcation plots. It has been observed that the fluctuations are modified from chaotic to ordered state with increase in the axial distance from cathode. Plasma parameters such as electron density ( n e ), electron temperature ( T e ) and deposition rate ( D r ) were measured and correlated with plasma fluctuations. It was found that more the deposition rate, greater the grain size, higher the electron density, higher the electron temperature and more chaotic the oscillations near the cathode. This observation could be helpful to the thin film technology industry to optimize the required film.